Respuesta :

Answer:

6x^3y

Step-by-step explanation:

Step by step solution :

Step  1  :

           y

Simplify   —

           3

Equation at the end of step  1  :

                y

 ((18 • (x2)) • —) • x

                3

Step  2  :

Equation at the end of step  2  :

             y

 ((2•32x2) • —) • x

             3

Step  3  :

Dividing exponents :

3.1    32   divided by   31   = 3(2 - 1) = 31 = 3

Equation at the end of step  3  :

 6x2y • x

Step  4  :

Multiplying exponential expressions :

4.1    x2 multiplied by x1 = x(2 + 1) = x3

Final result :

 6x^3y

When simplified, the answer is 6x3y

ACCESS MORE